Brain stem auditory evoked responses in chronic alcoholics. Issue 11 (November 1985) - Chan, Y W; McLeod, J G; Tuck, R R; Feary, P A
Abstract : Brain stem auditory evoked responses (BAERs) were performed on 25 alcoholic patients with Wernicke-Korsakoff syndrome, 56 alcoholic patients without Wernicke-Korsakoff syndrome, 24 of whom had cerebellar ataxia, and 37 control subjects. Abnormal BAERs were found in 48% of patients with Wernicke-Korsakoff syndrome, in 25% of alcoholic patients without Wernicke-Korsakoff syndrome but with cerebellar ataxia, and in 13% of alcoholic patients without Wernicke-Korsakoff syndrome or ataxia. The mean value of the I-V interval was prolonged in all patient groups. There were more patients with prolonged I-V and I-III intervals in the Wernicke-Korsakoff syndrome group than in the group without the syndrome. The I-III interval was prolonged in 32% of those with Wernicke-Korsakoff syndrome but in only 6% of alcoholics without the syndrome. These abnormalities improved following thiamine treatment and abstinence from alcohol. The presence of prolonged I-III interval in an alcoholic should raise the possibility of Wernicke's encephalopathy.